A Multicenter, International Collaborative Study for American Joint Committee on Cancer Staging of Retinoblastoma. Part II: Treatment Success and Globe Salvage - Singh Tomar, Ankit (2020)
Purpose: To evaluate the ability of the 8th edition of the American Joint Committee on Cancer (AJCC) Cancer Staging Manual to estimate metastatic and mortality rates for children with retinoblastoma(RB).Design: International, multicenter, registry-based retrospective case series PARTICIPANTS: 2190 patients from 18 ophthalmic oncology centers from 13 countries over 6 continents.Methods: Patient-specific data fields for RB were designed by participating eye cancer specialists. All RB patients with adequate records to allow tumor staging by the AJCC criteria and follow-up for metastatic disease were studied.Main outcome measures: Metastasis-related 5- and 10-year survival data after initial tumor staging were estimated with the Kaplan-Meier method depending on AJCC clinical (cTNM) and pathological (pTNM) tumor, node, metastasis category and age, tumor laterality, and presence of heritable trait.Results: Of the 2190 patients, the records of 2085 patients(95.2%) with 2905 eyes were complete. The median age at diagnosis was 17.0 months. 1260 (65.4%) had unilateral RB. Amongst the 2085 patients, tumor categories were cT1a in 55 (2.6%), cT1b 168 (8.1%), cT2a 197 (9.4%), cT2b 812 (38.9%), cT3 835 (40.0%) and cT4 in 18 (0.9%) patients. Of these, 1397 eyes in 1353 patients(48.1%) were treated with enucleation. One hundred and nine patients (5.2%) developed metastases and died. The median time(n=92) from diagnosis to metastasis was 9.50 months. The 5- year Kaplan-Meier cumulative survival estimates by clinical tumor categories were 100% for category cT1a, 98% (95% confidence interval[CI], 97-99) for cT1b and cT2a, 96% (95% CI, 95-97) for cT2b, 89%(95% CI, 88-90) for cT3 tumors, and 45%(95% CI, 31-59) for cT4 tumors, respectively. Risk of metastasis increased with increasing cT (and pT) category(p < .001). Cox proportional hazards regression analysis confirmed a higher risk of metastasis in category cT3 (hazard rate [HR], 8.09; 95% CI, 2.55-25.70; p<0.001) and cT4 (HR, 48.55; 95% CI, 12.86-183.27; p< 0.001) compared to category cT1. Age, tumor laterality and presence of heritable trait did not influence the incidence of metastatic disease.Conclusion: Multicenter, international, internet-based data sharing facilitated analysis of the 8th edition AJCC RB Staging System for metastasis-related mortality and offered a proof of concept yielding quantitative, predictive estimates per category in a large, real life, heterogenous RB patient population.